2013
DOI: 10.1179/1939787913y.0000000007
|View full text |Cite
|
Sign up to set email alerts
|

Compaction characteristics of fine grained soil and rice husk ash mixture

Abstract: This study presents the compaction characteristics of fine grained soil and rice husk ash (RHA) mixture. Three types of fine grained soils viz., montmorillonite clay, kaolinite clay, and one local soil has been used in the present study. From the compaction tests results it is observed that with increase in RHA content (0-30%) maximum dry density (MDD) decreases and also optimum moisture content (OMC) increases irrespective of types of fine grained soil. Based on the experimental data, a number of linear regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…In series A, compaction tests have been performed with varying compaction energies in a wide range (2700 kJ/m 3 , 594 kJ/m 3 and 300 kJ/m 3 ) and varying fly ash content (0%, 5%, 10%, 15%, 20% and 25%) to study the effect of compaction energy and fly ash content on fly ash clay mixture. A number of researchers (Daniel and Benson, 1990;Boltz et al, 1998;Bera et al, 2007;Bera and Ghosh, 2011;Bera, 2014) considered all three types of laboratory compaction tests; i.e., modified proctor test, standard proctor test and reduced proctor test in their studies. In series B, standard proctor compaction test has been performed on three types of clay with fly ash content (0-25%) for two types of fly ash (BTPS and BBTPS).…”
Section: Experimental Program and Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In series A, compaction tests have been performed with varying compaction energies in a wide range (2700 kJ/m 3 , 594 kJ/m 3 and 300 kJ/m 3 ) and varying fly ash content (0%, 5%, 10%, 15%, 20% and 25%) to study the effect of compaction energy and fly ash content on fly ash clay mixture. A number of researchers (Daniel and Benson, 1990;Boltz et al, 1998;Bera et al, 2007;Bera and Ghosh, 2011;Bera, 2014) considered all three types of laboratory compaction tests; i.e., modified proctor test, standard proctor test and reduced proctor test in their studies. In series B, standard proctor compaction test has been performed on three types of clay with fly ash content (0-25%) for two types of fly ash (BTPS and BBTPS).…”
Section: Experimental Program and Experimental Methodsmentioning
confidence: 99%
“…Detailed study on compaction characteristics of pond ash has been performed by Bera et al (2007). Bera (2014) studied the compaction characteristics of fine grained soil rice husk mixture. However, detailed study on compaction characteristics of fly ash clay mixture is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the study of waste treatment plants concerned with soil pollution and the harmful effects on the environment effects is essentially monitored periodically to ensure the different types of soil characteristics and their strengths are studied thoroughly by qualified and essential team members during the experimentation process (Sharma and Sharma, 2021). The latest software was employed to get adequate results and past results of the soil permeability and its corrosion resistances throughout the concrete materials; flitched materials concerning the different densities ranging from 10 g/m 3 to 100 kg/m 3 are ensured with the help of OSTU technology followed by (Gupta et al, 2020), According to the (Arun et al, 2017), the gradual failures in the soil were found in the order of 5 to 10% compared to last two years; due to the lack of awareness of strengthen characteristics of the lake soil compared to the industry soil; the fragmented release of these minute diffractions defects the entire construction buildings resulting in the high maintenance costs compared to brick concentrates. Hence, it is required to study the properties of the soil, followed by erosion testing, corrosion testing, absorption tests, and diffraction stages.…”
Section: Introductionmentioning
confidence: 99%
“…For both treated and untreated soil compaction, compaction energy is a critical element. High compaction energy applied to the soil produces more densification, and thus a higher maximum dry density [1]. Many scientists have investigated compaction energy's impact on the engineering characteristics of both unstabilized and stabilized soils.…”
Section: Introductionmentioning
confidence: 99%
“…Variations of MDD, OMC, CBR SP, and PS resulting from the compactive efforts raising and quarry dust percentage are statistically significant at a 5% level. Bera (2014) [1] presented the compaction parameter variations of grained soil (fine) treated by rice husk ash. Based on the findings, he created linear regression analyses to estimate the density and moisture content of the soil-RHA mixture and drew the following conclusions: (1) the density of soil reduces when the addition proportion increases.…”
Section: Introductionmentioning
confidence: 99%